SUPLEMENTASI KALSIUM UNTUK PENCEGAHAN PREEKLAMPSIA: Calcium Supplementation and Prevention of Preeclampsia (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Preeclampsia is a form of hypertension in pregnancy. Mineral and nutritional factors play a role in the etiology of preeclampsia. There is a potential benefit of taking calcium supplements during pregnancy, namely prevents preeclampsia by preventing a decrease in serum calcium levels so there is a decrease in intracellular calcium concentration, which will reduce smooth muscle contractility and stimulate vasodilation. Purpose: To know the effectiveness of giving calcium supplements to the prevention of preeclampsia in pregnant women. Methods: Searched on pubmed, google scholar and cochrane. Results: The results from a Systematic Review found statistically high doses of calcium supplements (1.2-2 g/day), moderate doses (0.6-1.2 g/day), and low doses (<0.6 g/day). May reduce the risk of preeclampsia. Conclusion: Calcium shows effectiveness against preeclampsia prevention in pregnant women.